Perception of Teachers in Rural Educational Institutions on the School Role of Boys and Girls from 6-11 Years Old in the Context of the Armed Conflict in Catatumbo (Cuidado y Ocupación Humana, 2025)
The armed conflict in Colombia has been a rather complex problem, affecting society in many ways, including the school environment. Approximately 75 million school-aged children live in countries affected by conflict, including 12 million refugees, whose access to education in low-resource and conflictaffected contexts is crucial for their comprehensive development. Therefore, the present study aimed to describe the perception of teachers from rural educational institutions about the school role performance of children aged 6-11 in the context of the armed conflict in Catatumbo. The methodology used was a qualitative phenomenological approach and included the participation of 10 teachers who work with children aged 6 to 11 in an educational institution in Catatumbo, who were given a semistructured interview. The results allowed us to determine the perception of teachers about the school role of children in these conflict zones and to identify educational strategies that teachers apply to support children's school performance, establishing the situations that most influence said performance. In conclusion, the results of the study suggest the importance of implementing educational and psychosocial support strategies that address the specific needs of children in contexts of armed conflict.
Keywords: rural education; school role; armed conflict; educational strategies